2007
DOI: 10.1097/01.ccm.0000260633.66384.fb
|View full text |Cite
|
Sign up to set email alerts
|

Role of transcranial Doppler in neurocritical care

Abstract: Transcranial Doppler has several practical applications in neurocritical care. It has its main application in the diagnosis and monitoring of vasospasm in patients with subarachnoid hemorrhage. In addition, it holds promise for the detection of critical elevations of intracranial pressure. Its ability to measure CO2 reactivity and autoregulation may ultimately allow intensivists to optimize cerebral perfusion pressure and ventilatory therapy for the individual patient. Transcranial Doppler findings of brain de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
65
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(67 citation statements)
references
References 55 publications
(58 reference statements)
0
65
0
2
Order By: Relevance
“…The fact that TCD is a noninvasive and sensitive method to assess the intracranial dynamics in TBI makes it an ideal tool in neurointensive care units (NICU) (2,17,30). The use of TCD as a predictor of ICP was first described by Klingerhofer et al They have shown that Middle cerebral artery (MCA) flow velocities and PI may help to assess the progression of the injury, correlate well with ICP and guide the treatment protocols if invasive ICP measurements are not available at the NICU (2,11,12,19,30). Several studies have focused on the changes in MCA flow velocity measurements after head injuries and they reinforce the use of TCD together with multimodality monitoring to understand the patterns of perfusion, oxygenation and autoregulation (8,15,22,26).…”
Section: Introductionmentioning
confidence: 99%
“…The fact that TCD is a noninvasive and sensitive method to assess the intracranial dynamics in TBI makes it an ideal tool in neurointensive care units (NICU) (2,17,30). The use of TCD as a predictor of ICP was first described by Klingerhofer et al They have shown that Middle cerebral artery (MCA) flow velocities and PI may help to assess the progression of the injury, correlate well with ICP and guide the treatment protocols if invasive ICP measurements are not available at the NICU (2,11,12,19,30). Several studies have focused on the changes in MCA flow velocity measurements after head injuries and they reinforce the use of TCD together with multimodality monitoring to understand the patterns of perfusion, oxygenation and autoregulation (8,15,22,26).…”
Section: Introductionmentioning
confidence: 99%
“…18 TCD has the advantage of being a bedside examination, repeatable, and less expensive that CTA. 19 A new TCD technology, power motion mode Doppler (PMD-TCD), is thought to increase the speed by which acoustic windows are found and arteries. 20,21 However, the rate of successful identification of obstructed intracranial vessels with PMD-TCD only, when compared with CTA, is not known.…”
mentioning
confidence: 99%
“…Despite the widespread use of triple H therapy to prevent vasospasm after SAH, only a few studies have questioned its efficacy and there is insufficient data of evidence based medicine to make recommendations for the preventive use of triple H therapy in SAH patients (26,36).…”
Section: The Study Findingsmentioning
confidence: 99%